2010
DOI: 10.1186/1755-8794-3-56
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in whole blood identifies distinct biological pathways associated with obesity

Abstract: BackgroundObesity is reaching epidemic proportions and represents a significant risk factor for cardiovascular disease, diabetes, and cancer.MethodsTo explore the relationship between increased body mass and gene expression in blood, we conducted whole-genome expression profiling of whole blood from seventeen obese and seventeen well matched lean subjects. Gene expression data was analyzed at the individual gene and pathway level and a preliminary assessment of the predictive value of blood gene expression pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 58 publications
7
69
0
1
Order By: Relevance
“…The black module was dominated by a ribosome and proteasome-related gene signature. Interestingly, similar signatures have been reported in two blood expression studies of obesity unrelated to asthma: a ribosome pathway signature defined in peripheral whole blood samples was also associated with obesity in a small gene expression study in 17 obese and 17 non-obese subjects [38], and a second study by the same group showed a proteasome signature in whole blood comparing nine diet-sensitive and nine diet-resistant obese subjects [39]. Given that both these biological processes are of fundamental importance to cellular function generally, it is unclear whether their implication in our study is specific to asthma and obesity together (perhaps reflecting fundamental differences in cellular metabolic demands in these patients) [40,41], or whether these associations reflect more generic patterns of cellular activity or stress seen in obese patients [42,43].…”
Section: Discussionsupporting
confidence: 71%
“…The black module was dominated by a ribosome and proteasome-related gene signature. Interestingly, similar signatures have been reported in two blood expression studies of obesity unrelated to asthma: a ribosome pathway signature defined in peripheral whole blood samples was also associated with obesity in a small gene expression study in 17 obese and 17 non-obese subjects [38], and a second study by the same group showed a proteasome signature in whole blood comparing nine diet-sensitive and nine diet-resistant obese subjects [39]. Given that both these biological processes are of fundamental importance to cellular function generally, it is unclear whether their implication in our study is specific to asthma and obesity together (perhaps reflecting fundamental differences in cellular metabolic demands in these patients) [40,41], or whether these associations reflect more generic patterns of cellular activity or stress seen in obese patients [42,43].…”
Section: Discussionsupporting
confidence: 71%
“…Transcriptional profiling studies in peripheral blood leukocytes may provide some evidence on the relationship between LY86 gene methylation and gene expression. We searched the Gene Expression Omnibus (GEO) database and identified a dataset (Ghosh et al, 2010; GSE18897) that included genome-wide gene expression data in peripheral blood samples from 20 obese and 20 lean adults. In line with our findings that obese cases had higher methylation levels of the LY86 gene, in this gene expression dataset, the expression level of LY86 gene was lower in the obese cases than in the lean controls, although the difference did not reach significance (309 ± 78 vs. 340 ± 75, p = .18).…”
Section: Discussionmentioning
confidence: 99%
“…This is further highlighted by the complex patterns and variability in magnitude of expression changes for a transcript in different tissues. Analysis of the effects of the GWAS SNPs on gene expression in lymphocytes has been suggested since this is a readily accessible source of RNA, and differences in lymphocyte gene expression between lean and obese individuals have been detected [35]. This may be useful if the SNPs affect basal transcription of a gene, but will not be useful if the SNPs affect enhancer elements.…”
Section: Discussionmentioning
confidence: 99%